Evaluation of a novel ELISA test using synthetic mycolic acid antigens for serodiagnosis of non-tuberculous mycobacterial (NTM) infections. Issue 3 (10th January 2023) - Bashford, Julia; Flowers, William; Haworth, Charles; Ryan, Judy; Cervi, Anna; Dulayymi, J R Al; Mason, Paul S; Plank, Ashley; Baird, Mark; Floto, Andres
Abstract : The diagnosis of non-tuberculous mycobacteria (NTM) is a particular challenge in people with cystic fibrosis. Current standard diagnostic approaches rely on serial sputum culture, which is resource demanding, dependent on patient expectoration and may be compromised by excessive decontamination, conventional bacterial overgrowth and masking by concomitant oral and nebulised antibiotics. An alternative rapid, reliable and inexpensive diagnostic method is therefore urgently needed. Serum of patients with Mycobacterium abscessus infection and chronic suppurative lung disease without NTM infection was tested against an array of novel synthetic mycolic acids, identical or similar to natural components of mycobacterial cell walls, and glycopeptidolipid (GPL)-core antigen, which has previously been investigated in Mycobacterium avium pulmonary infection. Diagnostic accuracy of individual antigens and combination of various antigens were calculated. An ELISA using individual trehalose dimycolates and GPL-core antigen was able to effectively distinguish serum from infected and non-infected individuals with a specificity of 88% and a sensitivity of up to 88%, which increased to 88% sensitivity and 93% specificity by combining several antigens in the test. These results suggest synthetic mycolic acid antigens, used individually or in combination with GPL-core antigen could be successfully used to distinguish patients with M. abscessus infection from disease controls.